PENGEMBANGAN VIRTUAL JOYSTICK PADA GAME VIRTUAL BIOTOPE MENGGUNAKAN METODE DESIGN THINKING - Nuruzh Zhohiril Islami, - (2023)
"Virtual Biotope" is a mobile 3D serious game that aims to raise awareness about the existence of Kampung Blekok and its birds. The game faces challenges due to limited screen space in a portrait-orientation. This research is focused on designing and evaluating a suitable virtual joystick for this game. Design thinking is used as a method to identifying issues and generating solutions through iterative development. Through the design thinking process, floating joystick is re-developed for Virtual Biotope, and fixed joystick is used as comparison, derived from alternative solutions of virtual joystick issues in "Virtual Biotope". Both designs are evaluated by 11 participants based on usability aspects such as comfort, fatigue, ease of learning, and satisfaction. ISO 9241-411 standards are used to assess comfort and fatigue, while the Usefulness, Satisfaction, Ease of Use (USE) questionnaire measures ease of learning and satisfaction. The findings indicate that both virtual joystick designs have relatively high scores across these aspects, with no significant difference between the two. The scores for each aspect are as follows for fixed joystick versus floating joystick: 4.09 vs. 4.16 for the general aspect, 4.09 vs. 4.22 for fatigue, 4.07 vs. 4.36 for ease of learning, and 3.85 vs. 4.00 for satisfaction. From this research, it can be concluded that design thinking can provide solutions to virtual joystick issues for portrait-oriented 3D games, utilizing both fixed and floating joystick designs. These solutions were well-received by users, and the recommendation of the floating joystick design for "Virtual Biotope" has been proven effective.